Thermal enhancement analysis and geometric optimization research on the imping-jet double-layer nested microchannel heat sinks with upper streaming block - Zhou, Tao; Xiang, Shiyang; Shao, Xiaodong; Liu, Huanling; Shen, Han (International communications in heat and mass transfer, 2025)
This study investigates a novel design which utilizes an upper streaming block to enhance the thermal performance of imping-jet nested microchannel heat sink (IDN-MHS) by simulations and experimental verification. Compared with the classic IDN-MHS models, the imping-jet nested microchannel heat sink with an upper streaming block (IDN-MHS-HUD) shows significant capacity in heat dissipation. A 3-Dimensional printing technique was used in experimental tests to illustrate the numerical simulation results. Experimental results are well-aligned with numerical simulations, which show that the model with the best overall thermal performance is IDN-MHS-HUD_14. The pressure drop penalty characteristic of IDN-MHS-HUD_14 is superior to that of the reference model of IDN-MHS, exhibiting a 15 % reduction in pressure drop penalty compared with the latter. Also, the Nusselt number of the model is 7.94 % higher than that of the reference model. However, in the IND-MHS-HUD model, the exit location of the upper plate is not the optimum solution. Therefore, based on the enhanced model of IDN-MHS-HUD_14, further optimizations were conducted, whose locations of exits were altered to the position x1 equals 2.1 and x2 equals 4.0 through NSGA-II optimization to obtain the optimal combination. And the calculation results show that Tmax and Pmax are reduced by 1.33 % and 17.54 % respectively compared with the initial design, denoting that its heat dissipation capacity outperforms considerably that of IDN-MHS-HUD_14. •A design utilizing upper streaming block in IDN-MHS enhances the thermal characteristics.•IDN-MHS-HUD's working conditions significantly effect thermal-dynamic performance.•There is an optimal working condition to reach the best overall thermal performance.•NSGA-II is presented furtherly to obtain the optimal geometry.